The first detection of Leishmania major in naturally infected Sergentomyia minuta in Portugal - Campino, Lenea (2018)
Phlebotomine sandflies of the genus Sergentomyia are widely distributed throughout the Old World. It has been suggested that Sergentomyia spp are involved in the transmission of Leishmania in India and Africa, whereas Phlebotomus spp are thought to be the sole vectors of Leishmania in the Old World. In this study, Leishmania major DNA was detected in one Sergentomyia minuta specimen that was collected in the southern region of Portugal. This study challenges the dogma that Leishmania is exclusively transmitted by species of the genus Phlebotomus in the Old World.